Copper(I)‐Catalyzed Reductive Cross‐Coupling of N‐Tosylhydrazones with Amides: A Straightforward Method for the Construction of C(sp3)N Amide Bonds from Aldehydes. Issue 16 (27th October 2015) - Xu, Peng; Han, Fu‐She; Wang, Yan‐Hua
Abstract: A method for the one‐pot synthesis of substituted amides from aldehydes and amides is presented. Namely, condensation of aldehydes with N ‐tosylhydrazide generated the N ‐tosylhydrazones which were then reductively cross‐coupled in situ with primary or secondary amides in the presence of a copper catalyst to afford secondary or tertiary amides, respectively. The reaction proceeded efficiently for a wide range of aldehydes and amides under the optimized conditions, i.e., 10 mol% of tetrakis(acetonitrile)copper(I) tetrafluoroborate [Cu(CH3 CN)4 BF4 ], 1 mol% of tetra‐ n ‐butylammonium iodide [( n‐ Bu)4 NI], and sodium hydroxide [NaOH] as base in tetrahydrofuran (THF) at 80 °C. As a result, the method provides a straightforward route for the synthesis of substituted amides from readily available aldehydes via a transition metal‐catalyzed C( sp 3 )N amide bond forming reaction. Abstract :